The answer is
Z(2xy-3y+4x)
Hope this helps
1) Solving
we get ![(a+b)(4-c)](https://tex.z-dn.net/?f=%28a%2Bb%29%284-c%29)
2) Solving
we get ![8(2a^4-b)](https://tex.z-dn.net/?f=8%282a%5E4-b%29)
3) Solving
we get ![(x-3)(x-5)](https://tex.z-dn.net/?f=%28x-3%29%28x-5%29)
Step-by-step explanation:
We need to solve the following expressions:
1) ![4a+4b-ac-bc](https://tex.z-dn.net/?f=4a%2B4b-ac-bc)
We will solve this expression by factoring common terms:
![4a+4b-ac-bc](https://tex.z-dn.net/?f=4a%2B4b-ac-bc)
Factoring 4 from 4a+4b and -c from -ac-bc
![4(a+b)-c(a+b)](https://tex.z-dn.net/?f=4%28a%2Bb%29-c%28a%2Bb%29)
Taking common term
![(a+b)(4-c)](https://tex.z-dn.net/?f=%28a%2Bb%29%284-c%29)
2) ![16a^4-8b](https://tex.z-dn.net/?f=16a%5E4-8b)
We will solve this expression by factoring common terms:
![16a^4-8b](https://tex.z-dn.net/?f=16a%5E4-8b)
Taking 8 as common term:
![8(2a^4-b)](https://tex.z-dn.net/?f=8%282a%5E4-b%29)
3) ![x^2-8x+15](https://tex.z-dn.net/?f=x%5E2-8x%2B15)
We can solve the expression by breaking the middle term into 2
![x^2-3x-5x+15\\Finding\,\,common:\\=x(x-3)-5(x-3)\\=(x-3)(x-5)](https://tex.z-dn.net/?f=x%5E2-3x-5x%2B15%5C%5CFinding%5C%2C%5C%2Ccommon%3A%5C%5C%3Dx%28x-3%29-5%28x-3%29%5C%5C%3D%28x-3%29%28x-5%29)
Keywords: Finding factors
Learn more about Finding factors at:
#learnwithBrainly
Answer:
Step-by-step explanation:
Total money raised = 658 + 95.60 = $ 753.60
donated to each charity = 753.60/12 = $62.80
Answer:
top god's menu back door distract 9 call scars double knot thunderous gone away gone day SKZ ALL AROUND THE WORLD